Meta-Analysis of Stunting Eradication Policy: A Review of National Policy Implementation Impact in Indonesia - Dinda Rosanti Salsa Bela (CV. Abhinaya Indo Group, 2025)
This study aims to analyze the implementation of stunting control policies in Indonesia, where the focus of this study is the effectiveness of the program and the challenges in achieving national targets in stunting control. This study uses a qualitative research method by adopting a literature review approach. The research data were obtained through bibliometric analysis of 123 Scopus-indexed scientific documents over the past 10 years or from 2015 to 2025. This study uses the approach of public policy adaptation theory in the VUCA. The results of the study indicate that although the national stunting rate shows a positive trend, significant regional disparities still occur. Therefore, the author concludes that effective stunting control requires targeted intervention from the government as a policy maker. Including encouraging inter-sectoral collaboration to achieve the goal of national stunting control, so that the government can ensure optimal growth and development for future generations.